Mental Distress in Rural Areas of Indonesia - Saifullah, Azam David; Latifah, Nur; Artanti, Eria Riski; Cahyani, Kadek Dewi; Rahayu, Umi; Paramarta, Lalitya; Izzati, Rahma Mahdia; Priharjo, Robert; Warsini, Sri (Department of Nursing, Faculty of Medicine, Diponegoro University, 2020)
Background: There is a higher prevalence of mental distress in rural areas compared to urban areas in Indonesia. The rural areas of Indonesia have various socio-demographic and sophisticated cultural characteristics, but less exposed to foreign cultures. Thus, the study about the prevalence, associated factors, and predictors of mental distress in rural areas is necessary.Purpose: This study aimed to identify the population's status and related factors of mental distress in rural areas in Indonesia.Methods: A descriptive cross-sectional study was conducted to achieve the aims of the study. An Indonesian version of the Self-Rated Questionnaire, consisting of 20 items, was used to measure mental distress status of population in rural areas in Yogyakarta, Indonesia. A number of 872 records were included and analyzed using both univariate and bivariate analyses in this study.Results: The prevalence of mental distress in this population was 6%. The correlated factors of mental distress were age (Ï‡2=6.93, p=0.01), gender (Ï‡2=0.07, p=0.03), occupation (Ï‡2=0.26, p=0.02), housing dimension (Ï‡2=5.45, p=0.02), and illness status (Ï‡2=0.01, p<0.01).Conclusion: The prevalence of mental distress in rural areas of Indonesia is relatively lower than that of the national level. Future mental health programs may be focused on improving mental health on the elderly, male, vulnerable workers, overcrowded housing, and people who got a chronic illness.